Proceedings of the 6th International Workshop on Audio/Visual Emotion Challenge 2016
DOI: 10.1145/2988257.2988266
|View full text |Cite
|
Sign up to set email alerts
|

Depression Assessment by Fusing High and Low Level Features from Audio, Video, and Text

Abstract: International audienceDepression is a major cause of disability world-wide. The present paper reports on the results of our participation to the depression sub-challenge of the sixth Audio/Visual Emotion Challenge (AVEC 2016), which was designed to compare feature modalities ( audio, visual, interview transcript-based) in gender-based and gender-independent modes using a variety of classification algorithms. In our approach, both high and low level features were assessed in each modality. Audio features were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Speech technology offers promise because speaking is natural, can be used at a distance, requires no special training, and carries information about a speaker's state. A growing line of AI research has shown that depression can be detected from speech signals using natural language processing (NLP), acoustic models, and multimodal models [3], [4], [5], [6], [7], [8], [9], [10]. Common evaluations with shared data sets, features, and tools have recently led to progress, especially in modeling methods [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Speech technology offers promise because speaking is natural, can be used at a distance, requires no special training, and carries information about a speaker's state. A growing line of AI research has shown that depression can be detected from speech signals using natural language processing (NLP), acoustic models, and multimodal models [3], [4], [5], [6], [7], [8], [9], [10]. Common evaluations with shared data sets, features, and tools have recently led to progress, especially in modeling methods [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The present work introduced the GMHI, a novel variant of MHI and reported on the first application of LMHI [23] on the AVEC dataset. Another novelty of the proposed work is that categorical assessment of depressive symptomatology was performed using deep learning methods, for the first time on this dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In the DSC of AVEC'14, Pérez Espinoza et al [21] employed MHI, and for the same challenge, Jan et al [22] proposed the 1-D MHH, an extension of MHI, which is computed on the feature vector sequence instead of the intensity image. As part of their DSC-AVEC'16 participation, Pampouchidou et al [23] introduced Landmark Motion History Images (LMHI), which instead of considering intensities from image sequences, considers sequences of facial landmarks.…”
Section: Motion History Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Further, we add the presence of each topic to the feature vector, because each interview only covers a few topics and the topic presence might be correlated to the subject's status. Finally, gender is also a ached to the feature vector similar to the work in [22] and [14], where the authors report that gender information can greatly improve the classification performance. Figure 3 illustrates the structure of the feature vector and Table 2 shows the dimension of each feature category in the feature vector.…”
Section: Topic-wise Feature Mappingmentioning
confidence: 96%